General practitioners’ attitudes towards the management of dental conditions and use of antibiotics in these consultations: a qualitative study - Cope, Anwen L (BMJ Open, 2015)
OBJECTIVES: This study aimed to produce an account of the attitudes of general practitioners (GPs) towards the management of dental conditions in general practice, and sought to explore how GPs use antibiotics in the treatment of dental problems. DESIGN: Qualitative study employing semistructured telephone interviews and thematic analysis. PARTICIPANTS: 17 purposively sampled GPs working in Wales, of which 9 were male. The median number of years since graduation was 21. Maximum variation sampling techniques were used to ensure participants represented different Rural–Urban localities, worked in communities with varying levels of deprivation, and had differing lengths of practising career. RESULTS: Most GPs reported regularly managing dental problems, with more socioeconomically deprived patients being particularly prone to consult. Participants recognised that dental problems are not optimally managed in general practice, but had sympathy with patients experiencing dental pain who reported difficulty obtaining an emergency dental consultation. Many GPs considered antibiotics an acceptable first-line treatment for acute dental problems and reported that patients often attended expecting to receive antibiotics. GPs who reported that their usual practice was to prescribe antibiotics were more likely to prioritise patients’ immediate needs, whereas clinicians who reported rarely prescribing often did so to encourage patients to consult a dental professional. CONCLUSIONS: The presentation of patients with dental problems presents challenges to GPs who report concerns about their ability to manage such conditions. Despite this, many reported frequently prescribing antibiotics for patients with dental conditions. This may contribute to both patient morbidity and the emergence of antimicrobial resistance. This research has identified the need for quantitative data on general practice consultations for dental problems and qualitative research exploring patient perspectives on reasons for consulting. The findings of these studies will inform the design of an intervention to support patients in accessing appropriate care when experiencing dental problems.